What does budget 2007-08 offer women? - Mishra, Yamini; Jhamb, Bhumika (2007)
A closer look at the gender budgeting statement in the Union Budget 2007-08 reveals that programmes and allocations remain plauged by "mistakes", with several schemes wrongly prioritised as being exclusively for women. The fact that women have begun to figure in the annual financial exercise of the government is a laudable step, but there remains a need to prioritise women in all development schemes of the government. - Reproduced.
Keywords: Women - India; Budget - India; Budget